Methods of testing plastics. Optical and colour properties, weathering. Methods of exposure to laboratory light sources, (xenon arc lamp, enclosed carbon arc lamp, open-flame carbon arc lamp, fluorescent tube lamps) Part 5, (26th February 1982) - British Standards Institution,
No abstract available